Profiling of the Major Phenolic Compounds and Their Biosynthesis Genes in Sophora flavescens Aiton - Jeongyeo Lee; Jaeeun Jung; Seung-Hyun Son; Hyun-Bi Kim; Young-Hee Noh; Sung Ran Min; Kun-Hyang Park; Dae-Soo Kim; Sang Un Park; Haeng-Soon Lee; Cha Young Kim; Hyun-Soon Kim; et al. (The Scientific World Journal)
Sophorae Radix (Sophora flavescens Aiton) has long been used in traditional medicine in East Asia due to the various biological activities of its secondary metabolites. Endogenous contents of phenolic compounds (phenolic acid, flavonol, and isoflavone) and the main bioactive compounds of Sophorae Radix were analyzed based on the qualitative HPLC analysis and evaluated in different organs and at different developmental stages. In total, 11 compounds were detected, and the composition of the roots and aerial parts (leaves, stems, and flowers) was significantly different. trans-Cinnamic acid and p-coumaric acid were observed only in the aerial parts. Large amounts of rutin and maackiain were detected in the roots. Four phenolic acid compounds (benzoic acid, caffeic acid, ferulic acid, and chlorogenic acid) and four flavonol compounds (kaempferol, catechin hydrate, epicatechin, and rutin) were higher in aerial parts than in roots. To identify putative genes involved in phenolic compounds biosynthesis, a total of 41 transcripts were investigated. Expression patterns of these selected genes, as well as the multiple isoforms for the genes, varied by organ and developmental stage, implying that they are involved in the biosynthesis of various phenolic compounds both spatially and temporally.